Controllability and Observability (C.I.M.E. Summer Schools, 2011)
R.E. Kalman: Lectures on controllability and observability -- E. Kulikowski: Controllability and optimum contro -- A. Straszak: Supervisory controllabilityl -- L. Weiss: Lectures on controllability and observability.